Commenter et inciter à commenter les publications vidéo des chaînes de télévision sur Facebook : les cas de TF1, France 2 et M6 - Laurence Leveneur (Communiquer)
How the French Television channels TF1, France 2 and M6 try to generate online comments dedicated to their programs on social media, and specifically about their video publications on Facebook? How social media managers adjust to the platforms’ constraints and to the editorial policies of broadcasting companies? A semiotic analysis of the “screen writing process” observed on the Facebook pages of those channels, combined with a study of the type of video published and the rhetoric speeches that accompanies them, figures out an effort to maintain an editorial line. But the rhetoric speeches we studied have less influence on online comments compared to platform devices’ effects on media’s communication limited to certain types of posts. If Facebook presents itself as an agora, it must be noted the weakness of the interactions between the administrators of the accounts studied and the Internet users, and the importance of social grouping exchanges.